Comparison of immunohistochemistry and gene expression profiling subtyping for diffuse large B‐cell lymphoma in the phase III clinical trial of R‐CHOP ± ibrutinib. (3rd May 2021) - Balasubramanian, Sriram; Wang, Songbai; Major, Christopher; Hodkinson, Brendan; Schaffer, Michael; Sehn, Laurie H.; Johnson, Peter; Zinzani, Pier Luigi; Carey, Jodi; Shreeve, S. Martin; Sun, Steven; Gerecitano, John; et al.
Summary: We assessed the concordance between immunohistochemistry (IHC) and gene expression profiling (GEP) for determining diffuse large B‐cell lymphoma (DLBCL) cell of origin (COO) in the phase III PHOENIX trial of rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone (R‐CHOP) with or without ibrutinib. Among 910 of 1114 screened patients with non‐germinal centre B cell‐like (non‐GCB) DLBCL by IHC, the concordance with GEP for non‐GCB calls was 82·7%, with 691 (75·9%) identified as activated B cell‐like (ABC), and 62 (6·8%) as unclassified. Among 746 of 837 enrolled patients with verified non‐GCB DLBCL by IHC, the concordance with GEP was 82·8%, with 567 (76·0%) identified as ABC and 51 (6·8%) unclassified; survival outcomes were similar regardless of COO or treatment, whereas among patients with ABC DLBCL aged <60 years, the overall and event‐free survival were substantially better with ibrutinib versus placebo plus R‐CHOP [hazard ratio (HR) 0·365, 95% confidence interval (CI) 0·147–0·909, P  = 0·0305; HR 0·561, 95% CI 0·326–0·967, P  = 0·0348, respectively]. IHC and GEP showed high concordance and consistent survival outcomes among tested patients, indicating centralised IHC may be used to enrich populations for response to ibrutinib plus R‐CHOP.